The Effects of hydrotherapy on Guillain-Barré Syndrome after vaccination against Covid-19: Case report (Research, Society and Development, 2022)
Guillain-Barré Syndrome is a neurological disease of autoimmune character, commonly resulting from acute bacterial or viral diseases that affect mainly the peripheral nervous system. With the emergence of the Covid-19 pandemic, caused by the SARS-CoV-2 virus, the creation and application of immunizing vaccines to the world population became necessary. Despite the benefits, the administration of vaccines can have adverse reactions, which, in rare cases, trigger GBS. The present study is a descriptive and qualitative research, which aims to present the case report of a patient diagnosed with GBS after vaccination against Covid-19, who used hydrotherapy as a form of treatment. The hydrotherapy acted significantly on the GBS symptoms, being even more beneficial on the global functionality. Therefore, the hydrotherapy protocol in a continuous and disciplined way in the treatment of GBS showed significant functional improvement, contributing to a better quality of life for the patient.